2016
DOI: 10.1177/230949901602400109
|View full text |Cite
|
Sign up to set email alerts
|

Standard Preoperative Analgesia with or without Fascia Iliaca Compartment Block for Femoral Neck Fractures

Abstract: Purpose. To compare the visual analogue score (VAS) for pain in patients with femoral neck fracture who received standard preoperative analgesia with or without fascia iliaca compartment block (FICB). Methods. In patients with femoral neck fracture, 69 patients who received standard preoperative analgesia (regular paracetamol 1g 4 times a day, codeine 60 mg 4 times a day, and opioid 10 mg 2 hourly as required) were compared with 50 patients who received standard preoperative analgesia plus FICB. VAS for pain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…Among those studies reviewed, those that utilised ultrasound guidance and sampled a large patient population demonstrated the most significant positive effects of regional blockade. There is also consistent evidence that the use of regional nerve blocks can reduce the consumption of opiates following hip fracture , and reduce the incidence of opiate side‐effects and overdose .…”
Section: Methodsmentioning
confidence: 89%
“…Among those studies reviewed, those that utilised ultrasound guidance and sampled a large patient population demonstrated the most significant positive effects of regional blockade. There is also consistent evidence that the use of regional nerve blocks can reduce the consumption of opiates following hip fracture , and reduce the incidence of opiate side‐effects and overdose .…”
Section: Methodsmentioning
confidence: 89%
“…Williams et al [14] and Groot et al [15], in their respective studies, showed that FIB was better as compared to intravenous analgesics. Williams et al [14] used 30 mL of 0.25% levobupivacaine, resulting in a reduction of VAS score to less than 3 in 15 minutes, and analgesia lasted up to 8 hours as compared to intravenous opioids, with a P < 0.001 which was highly significant. This can be due to a slower onset but prolonged duration of action for levobupivacaine.…”
Section: Discussionmentioning
confidence: 98%
“…Bupivacaine has been used previously for analgesia in both the FNB and FIB [4,9,14,17,21]. With an onset of action between 2 and 5 minutes, the maximum plasma levels are reached in 15-30 minutes [22].…”
Section: Discussionmentioning
confidence: 99%
“…Other methods of analgesia, which have shown benefit in femoral neck fractures, include fascia iliaca blocks by reducing the need for additional opioid analgesia. 12 …”
Section: Introductionmentioning
confidence: 99%